Culture and the cognitive science of religion - Cresswell, James (Cultural dynamics of social representation, 2018)
Towards a cognitive science that doesn't alienate everyone except cognitive scientists -- Seriously, culture and language need to be taken seriously -- Don't throw the baby out with the bathwater I: development of religious belief -- Don't throw the baby out with the bathwater II: evolution and experience -- On being good researchers -- Does reality and/or god exist or not?